COMPUTER IMPLEMENTATION METHODS TECHNOLOGIES IN PROFESSIONAL TRAINING OF THE FUTURE TEACHER BY MEANS OF THE PROGRAM INTEL “LEARNING FOR THE FUTURE” (Pedagogy of Higher and Secondary Education, 2006)
The necessity of using the latest computer technologies during teacher’s professional training is considered the effectiveness is confirmed in the article.